Perbaikan Progresif Kardiomiopati Peripartum dengan Fraksi Ejeksi Awal Rendah - Christian Sunur; Bambang Hermawan; Dorothea Apitule (The Indonesian Heart Association, 2016)
Peripartum cardiomyopathy (PPCM) is a pregnancy-associated, idiopathic cardiomyopathy secondary to marked left ventricular dysfunction, which manifests between the last month of pregnancy and the first five months postpartum. While it is relatively rare, PPCM is associated with significant morbidity and can be fatal. Its diagnosis is often delayed because its symptoms closely resemble those within the normal spectrum of pregnancy and the postpartum period. When PPCM is misdiagnosed or is not diagnosed in time, the consequences for patients could be deadly. We present a rare case which was first misdiagnosed but had a continuous progressive recovery of LV systolic function (LVSF) within five years after it was finally diagnosed and treated.A 23 year-old female, P1A0, 8-weeks postpartum, was admitted to the emergency unit of our hospital because of dyspnea and fatigue, which developed three days after the delivery of her child. A week prior to delivery she was admitted to the hospital due to coughing, proteinuria and edema of her lower extremities. She was then diagnosed with severe preeclampsia. The patient, however, refused the administration of Magnesium-sulfate as a therapy because of personal reasons. 48 hours later, the patient was induced with oxytocin and she delivered a living female infant via vaginal delivery with no labor complications and was later discharged. Three days after delivery, the patient complained about having shortness of breath and fatigue. She went to a general practitioner who thought her symptoms were normal after a delivery. Two months later she went to an obstetric clinic for a check-up and was referred to the cardiology unit at our hospital. She stated that for the past two months, she had been experiencing symptoms such as exhaustion, palpitations, an inability to lay flat, decreased exercise tolerance and severe dyspnea.PPCM is a rare but potentially lethal disease that remains a challenge to diagnose, prognosticate, and treat. It is increasingly recognized that the condition is often diagnosed late which may indicate a poor prognosis. However, there are cases in which the initial severity of left ventricular dysfunction or dilatation is not necessarily predictive for long-term functional outcome.